TINGKAT PENGETAHUAN DAN KESEDIAAN MASYARAKAT MELAKUKAN VAKSINASI BOOSTER COVID-19 DI KELURAHAN JAMBANGAN KOTA SURABAYA - Maulana Fa’iq Effendi; Joko Wiyono; Arief Bachtiar; Maria Diah Ciptaning Tyas (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2023)
Not all Indonesians are willing to undergo the Covid-19 booster vaccination. One of the obstacles is the lack of public knowledge and trust due to negative issues surrounding booster vaccination. The purpose of this study was to determine the relationship between the level of knowledge and the willingness of the community in Jambangan Village, Surabaya City, to receive the Covid-19 booster vaccination. The design of this study was correlational research, and the data collection method used was cross-sectional. The sampling technique employed was purposive sampling, with a total of 61 respondents. Data management was conducted using the SPSS application, and the Spearman Rank Correlation Test was performed. The study's results indicated that the majority of respondents (68.8%) had a good level of knowledge. Moreover, most people in Jambangan village (63.9%) were willing to receive the booster vaccine. Data analysis revealed a significant correlation (p-value: 0.001) with OR: 171 and a 95% CI: 18.8 – 1641.9. In conclusion, there is a significant relationship between the level of knowledge and the willingness to receive booster vaccination in the community of Jambangan village, Surabaya City.